What Has Changed in the Behaviors of the Public After the COVID-19 Pandemic? A Cross-Sectional Study From the Saudi Community Perspective - Wajid, Syed; Samreen, Sana; Sales, Ibrahim; Bawazeer, Ghada; Mahmoud, Mansour Adam; Aljohani, Majidah A. (Frontiers in Public Health, 2022)
Background Coronavirus disease-2019 (COVID-19) is caused by severe acute respiratory syndrome-coronavirus (SARS-CoV) and represents a major public health threat that aggressively promotes increased morbidity and mortality. Changes in public behavior were more common during the pandemic to protect against the infection. Suboptimal behavioral practices for a specific disease would increase the susceptibility of the public to infection. This study aimed to determine changes in behaviors of the general public during the COVID-19 pandemic. Methods A cross-sectional study was conducted using an online questionnaire survey to determine the extent of public behavioral changes in Saudi Arabia during the COVID-19 pandemic. Data were collected with a self-reported survey, and analysis was conducted using Statistical Package for the Social Sciences version 26 (SPSS). A chi-square test was performed to determine the association among variables. A P ≤ 0.05 was considered statistically significant. Results Of 348 respondents, 244 (70.1%) were male, and 270 (77.6%) had a university degree. Approximately 48% used social media to seek COVID-19 information, and 36% (n = 124) avoided large gatherings. Approximately one-fourth of the respondents always avoided public transportation, while 65.8% reported avoiding traveling to infected areas. Of the participants, 33% always washed their hands, while 36% always used an alcohol-based sanitizer. There was a significant association between age group and employment status with respect to hand washing frequency (p < 0.05). There was also a significant association between age group (p < 0.0001) and employment status and wearing of face masks (p < 0.048). Conclusion This study highlights changes in the public's behaviors in Saudi Arabia during the COVID-19 pandemic for protection against the infection and reports acceptable preventative practices against COVID-19 in the Saudi community. Furthermore, continuous awareness of recommended protective measures for COVID-19 is still warranted.